2014
DOI: 10.1080/02687038.2014.910588
|View full text |Cite
|
Sign up to set email alerts
|

Functional disability in primary progressive aphasia

Abstract: Background: In primary progressive aphasia (PPA), assessment of language predominates over assessment of functional impairment in activities of daily living (ADLs) in clinical and research environments. Most of the knowledge on functional disability in PPA relies largely on anecdotal experience and limited numbers of studies published to date. Aims: (1) To describe the different patterns of ADL functional disability in the main PPA variants: semantic variant, nonfluent aphasia, and the more recently defined lo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
15
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 59 publications
(90 reference statements)
2
15
0
Order By: Relevance
“…Compared to the nfvPPA group, svPPA patients showed heightened Sensitivity to Details (e.g., “Is sensitive to misaligned objects such as paintings” and “Is rigid and particular on how items must be ordered”) and increased Hypersensitivity. The presence of these behaviours aligns well with studies of other rigid behaviours that have been reported in this group, such as sticking to fixed timetables or always requesting the same foods [12,29]. Group differences were also observed in the social domain, such that lvPPA patients showed an increase in Music Activities compared to nfvPPA patients.…”
Section: Discussionsupporting
confidence: 71%
See 2 more Smart Citations
“…Compared to the nfvPPA group, svPPA patients showed heightened Sensitivity to Details (e.g., “Is sensitive to misaligned objects such as paintings” and “Is rigid and particular on how items must be ordered”) and increased Hypersensitivity. The presence of these behaviours aligns well with studies of other rigid behaviours that have been reported in this group, such as sticking to fixed timetables or always requesting the same foods [12,29]. Group differences were also observed in the social domain, such that lvPPA patients showed an increase in Music Activities compared to nfvPPA patients.…”
Section: Discussionsupporting
confidence: 71%
“…Previous studies of the clinical characteristics of PPA subtypes reported changes beyond language skills, including other cognitive domains [6,7], psychiatric symptoms [8,10], social cognition [9,28], and functional abilities [12]. The present study is the first to demonstrate and quantify the presence of various “positive” behaviours by PPA subtype.…”
Section: Discussionmentioning
confidence: 69%
See 1 more Smart Citation
“…Behavioural changes are often evident at presentation in patients with svPPA, resembling behavioural variant FTD, but these behavioural changes do not seem to be relevant in predicting functional decline in svPPA. While marked behavioural changes are present in svPPA, they seem to somehow allow for continued participation in activities, albeit in a very rigid manner, instead of hindering their performance [22,23,24]. While there was a trend for global cognition to contribute to around a third of the variance in functional decline, the remaining factors which contribute to functional decline in svPPA remain unclear.…”
Section: Discussionmentioning
confidence: 99%
“…While these ADLS are often impaired initially, the typically slower rate of progression means that svPPA patients have preservation of basic ADLs for much longer when compared with bvFTD and nfvPPA patients [84,85]. Driving skills may remain intact until more moderate stages of the disease [86], and language-mediated activities may remain intact, despite a patient's inability to name items or communicate their intentions [86]. …”
Section: Semantic Variant Primary Progressive Aphasiamentioning
confidence: 99%